The Effect of Differential Weathering on The Magnetic Properties of Paleosols: A Case Study of Magnetic Enhancement vs. Magnetic Depletion in the Pleistocene Blackwater Draw Formation, Texas - Stine, J.; Geissman, J.W.; Sweet, D.E.; Baird, H. (Frontiers in Earth Science, 2021)
The type-section of the Blackwater Draw Formation (BDF) consists of a series of five paleosol horizons developed on eolian deposits and an overlying surficial soil. Previous work has shown that magnetic properties (e.g., χ, ARM, and IRM) as a function of depth in this type-section, display both magnetically enhanced and magnetically depleted signals for different paleosols. To better understand the magnetic mineralogy responsible for these varying responses, various rock-magnetic experiments, scanning electron microscopy, and Mössbauer spectroscopy were conducted on representative samples from the six soil units which constitute the BDF type-section. Our results show that sub-micron hematite (with a minor contribution from single-domain sized hematite (Hc = ~500 mT)) dominates all the soils in terms of weight percent concentration. Whereas, low coercivity (Hc = ~35 mT or less) magnetite/maghemitized-magnetite grains, largely in the PSD state (Mr/Ms=~0.14 +/- 0.03588, Hcr/Hc=~2.68 +/- 0.298789), dominate the magnetic signal. Magnetically depleted soils show a relatively higher proportion of goethite, while magnetically enhanced soils show an increased contribution from SP/SSD magnetite/maghemite phases. By combining our data-set with geochemically-derived climofunctions, we have correlated the magnetically preserved, depleted, and enhanced sections of the type-section to three distinct environmental phases (I-III). The basal sediments of Phase I displays relatively homogenous (neither enhanced nor depleted) magnetic properties due to relatively arid conditions and minimal alteration of southerly derive eolian sands. Conversely, Phase II-III represents a change in weathering intensities and provenance, resulting in a mix of southerly derived sands and northerly derived silts. Phase II, experiences greater precipitation levels, resulting in the dissolution of Fe-oxide phases and thus magnetic depletion. The uppermost Phase III experiences intermediate precipitation intensities resulted in magnetic enhancement. Using previously published age models we tentatively interpret these changing environmental conditions to be influenced by the Middle-Pleistocene Transition (1.2-0.7 Ma), where the Earth’s climatic cycles shifted from a ~41 kyr to ~100 kyr cycles. However, ambiguities persist due to uncertainties in the currently published age model. Due to the complexity of the magnetic signal, we recommend future studies utilize a holistic approach, incorporating rock-magnetic, geochemical, and microscopy observations for more accurate reconstruction of regional paleoenvironments.